Pengenalan Satwa Papua dan Status Konservasinya melalui Sosialisasi di Sekolah SMA Bintuni Papua Barat: Introduction to Papuan Animals and Their Conservation Status through Socialization at Bintuni High School, West Papua - Kawulur, Elda Irma Jeanne Joice; Massora, Maria; Sutarno, Simon; Lefaan, Paskalina Theresia; Panjaitan, Rawati; Salosa, Yenni; Ratnawati, Sita; Budirianto, Heru Joko (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2024)
Papua has a high level of species diversity and endemism. This community service activity (PKM) is motivated by the decreasing of Papua’s biodiversity due to anthropogenic activities and global warming, so it is necessary to make efforts to increase public awareness, especially among the children about the concept of protection, management, and use wisely and sustainably for Papua’s diversity. Therefore, we carried out socialization about the Papuan animals and their conservation status to students at SMA Negeri 1 and SMA YPPK St. Arnoldus Jansen in Bintuni Bay District, West Papua Province on 10-11 December 2021. Socialization activities involve lectures, questions, and answers, filling out questionnaires, and giving rewards. The results showed that 61.54% of participants did not know the conservation status of animals in Papua based on Indonesian and international regulations. In addition, as many as 87.18% of participants stated that some animals in Papua were sold in the market and participants also consumed some of these animals. However, the participants’ desire to protect Papua’s animals is quite high (94.87%).